Next-generation sequencing of the cerebrospinal fluid in the diagnosis of neurobrucellosis. (February 2018) - Fan, Siyuan; Ren, Haitao; Wei, Yanping; Mao, Chenhui; Ma, Zhenzi; Zhang, Lu; Wang, Li; Ge, Ying; Li, Taisheng; Cui, Liying; Wu, Honglong; Guan, Hongzhi
Highlights: Patients with dramatically different symptoms were diagnosed with neurobrucellosis. The patients were diagnosed using next-generation sequencing (NGS) of the cerebrospinal fluid (CSF). This is the first case series of neurobrucellosis diagnosed with NGS of the CSF. Abstract: Background: Brucellosis is the most common zoonotic infection in the world. Brucellosis with nervous system involvement is known as 'neurobrucellosis' (NB). The diagnosis of NB is difficult because its clinical manifestations are non-specific and the sensitivity of routine culture tests is low. Methods: Next-generation sequencing (NGS) of cerebrospinal fluid (CSF) was used to detect pathogens in patients with clinically suspected central nervous system (CNS) infections at a tertiary referral center in China between June 1, 2016 and June 1, 2017. The clinical characteristics and NGS results of patients with the diagnosis of NB were reviewed in this study. Results: Four patients were rapidly diagnosed with NB using NGS of the CSF in patients with clinically suspected CNS infections, although the clinical manifestations varied dramatically between these patients. NGS of the CSF revealed that the sequence reads identified that corresponded to Brucella species ranged from 11 to 104, with genomic coverage ranging from 0.043% to 0.4%. Rapid diagnosis led to prompt treatment with the appropriate antibiotics. Conclusions: This study demonstrates the power of NGS of the CSF coupled with a bioinformatic pipeline in the diagnosis of NB.